Fatal Breakthrough Mucormycosis in an Acute Myelogenous Leukemia Patient while on Posaconazole Prophylaxis - Kang, Seung Hun; Kim, Hyun Seon; Bae, Myoung Nam; Kim, Jihye; Yoo, Ji Yeon; Lee, Kwan Yong; Lee, Dong-Gun; Kim, Hee-Je (Infection & chemotherapy, 2015)
Posaconazole is a new oral triazole with broad-spectrum antifungal activity. Posaconazole has also shown a significant advantage of preventing invasive fungal infection compared to fluconazole or itraconazole in patients with prolonged neutropenia. Indeed, posaconazole has been commonly used for antifungal prophylaxis in patients undergoing remission induction chemotherapy for acute myelogenous leukemia or myelodysplastic syndrome. We experienced a case of fatal mucormycosis despite posaconazole prophylaxis. To our knowledge, this is the first reported case of fatal breakthrough mucormycosis in a patient receiving posaconazole prophylaxis during remission induction chemotherapy in Korea. This case demonstrated that breakthrough fungal infection can occurs in patients receiving posaconazole prophylaxis because of its limited activity against some mucorales.